SAPE’ TING DUA’ SUKU DAYAK KAYAAN MENDALAM - Dennis Hoogendyk, Fian Welliem; Mering, Aloysius; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe making process of Sape’ Ting Dua’, shortly, the instrument’s structure of Sape’ Ting Dua’ and its teqnique of Sape’ Ting Dua’ from Kayaan Mendalam tribe in Desa Datah Diaan that is the background of this writing. Specifically up to this point, this research is about how the structure of Sape’ Ting Dua’ instrument, how the process of making it, and how the technique of the instrument of Sape’ Ting Dua’ of Dayak Kayaan Mendalam tribe.The method of this research is descriptive with qualitative method and etnomusicology approach. The data of this research is the result of observation, documentations, the note book relates to the making process of Sape’ Ting Dua’. The resource data of this research is Dasius Simu’, Siprianus Gunung, Tarsisius Alel Sano. The data collection technique of this research is observation, interview, and documentations. The instrument of data collection of this research is the researcher as the main instrument. The validity data of this reserach is extended observation and triangulation technique. The technique of analisys data of this research is the analysis data during the collecting and after the analysis of collecting data. The result of this research is to describe how the short history of Sape’ Ting Dua, the making process of it, and the technique instruments of Sape’ Ting Dua’ of Dayak Kayaan Mendalam tribe.Sape’ Ting Dua’ is the instrument that has been a habit of people in Dayak Kayaan Mendalam sub tribe. In the process of making Sape’ Ting Dua’, this instrument uses the basic material of Medaang. The process of making this instrument was quite difficult because it uses tradtional method. In the system of tone, Sape’ Ting Dua’ has only five tone, they are do, mi, fa, sol, la (Pentatonic Scale). Keywords: Sape’ Ting Dua’ of Dayak Kayaan Mendalam tribe